Studies of the browsing and reproductive behaviour of the East African Dwarf goat - Wilson, P.N. (1957)
Behaviour studies were carried out for 24-hour periods on four groups of experimental goats. There were no major differences between the behaviour of the several animals within a group at any given trial, but there were small statistically significant differences in the times individual goats spent ruminating. The variability in behaviour of the same animal from one trial to the next was pronounced, but was accounted for mainly by differences within the sub-divisions of the major activities rather than in the major activities themselves. Trial to trial variation was greatest for the behaviour of the goats during the hours of darkness. The results indicate that certain differences in behaviour exist between the sexes. The male spent longer ruminating than the females, resulting in a narrower browsing to ruminating ratio for female goats of 1:2.8 - compared to 1: 3.7. The major differences in the behaviour pattern of high and low plane lactating dams were due to the different systems of management employed. The longer period at browse of the high plane group resulted in a narrower browsing to ruminating ratio of 1: 2.7 compared to 1: 6.3 for the low plane group. Ruminating times remained relatively constant for all groups. The differences in behaviour between high and low plane kids of similar ages were very small. As with their dams low plane kids had wider browsing ruminating ratios, 1:2.1compared to 1:1.7. The total feeding times of high and low plane kids were very similar, but low plane kids suckled their dams more frequently during the night than high kids. Observations on the plants eaten by goats showed that over half the browsing time was occupied eating leaves and shoots of trees and bushes, mostly throny Acacias. Grasses were eaten but generally only the inflorescence was eaten and there was no evidence of goats preventing grass establishment and spread. The preference of the goats was for succulent shoots at about head-height. Only very few species were consistently rejected. Observations on the reproductive behaviour of the goats showed that the mean gestation period was 146.5 days. Pregnant goats were occasionally willing to accept service, 14 such instances being proven. The mean number of services per kid born was 2.3.